Early Intrusion Detection System (IDS) using Snort and Telegram approach - Aan Erlansari; Funny Farady Coastera; Afief Husamudin (Soegijapranata Catholic University, 2020)
Computer network security is an important factor that must be considered. Guaranteed security can avoid losses caused by attacks on the network security system. The most common prevention against network attacks is to place an administrator, but problems will arise when the administrator is not supervising the network, so to overcome these problems a system called IDS (Intrusion Detection System) can detect suspicious activity on the network through automating the work functions of an administrator. Snort is one of the software that functions to find out the intrusion. Data packets that pass through network traffic will be analyzed. Data packets detected as intrusion will trigger alerts which are then stored in log files. Thus, administrators can find out intrusions that occur on computer networks, and the existence of instant messaging applications can help administrators to get realtime notifications, one of which is using the Telegram application. The results of this study are, Snort able to detect intrusion of attacks on computer networks and the system can send alerts from snort to administrators via telegram bot in real-time.